2014
DOI: 10.1002/anie.201402050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Uranium(II) Monoarene Complex Supported by δ Backbonding

Abstract: The low-temperature (<-35 °C) reduction of the trivalent uranium monoarene complex [{((Ad,Me) ArO)3 mes}U] (1), with potassium spheres in the presence of a slight excess of 2.2.2-cryptand, affords the quantitative conversion of 1 into the uranium(II) monoarene complex [K(2.2.2-crypt)][(((Ad,Me) ArO)3 mes)U] (1-K). The molecular and electronic structure of 1-K was established experimentally by single-crystal X-ray diffraction, variable-temperature (1) H NMR and X-band EPR spectroscopy, solution-state and solid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
249
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(283 citation statements)
references
References 65 publications
23
249
0
8
Order By: Relevance
“…[1] Subsequently, as econd example was obtained by Meyer and co-workers in at ris(aryloxide)arene ligand environment by potassium reduction of [( Ad,Me ArO) 3 mes]U [Eq. (2)]. [2] These reactionsa re variations of reductionse xamined with Cp'' 3 M[ Cp'' = C 5 H 3 (SiMe 3 ) 2 ; M = La [3] and Th [4] ]a nd with Cp' 3 Ln [5] to make new + 2i ons of the rare earth metals and thorium as depicted in Equation (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Subsequently, as econd example was obtained by Meyer and co-workers in at ris(aryloxide)arene ligand environment by potassium reduction of [( Ad,Me ArO) 3 mes]U [Eq. (2)]. [2] These reactionsa re variations of reductionse xamined with Cp'' 3 M[ Cp'' = C 5 H 3 (SiMe 3 ) 2 ; M = La [3] and Th [4] ]a nd with Cp' 3 Ln [5] to make new + 2i ons of the rare earth metals and thorium as depicted in Equation (3).…”
Section: Introductionmentioning
confidence: 99%
“…(2)]. [2] These reactionsa re variations of reductionse xamined with Cp'' 3 M[ Cp'' = C 5 H 3 (SiMe 3 ) 2 ; M = La [3] and Th [4] ]a nd with Cp' 3 Ln [5] to make new + 2i ons of the rare earth metals and thorium as depicted in Equation (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent work has shown that ligand fields can be used to tune lanthanide redox chemistry 65,[104][105][106][107][108][109] and ground state electronic configurations. [110][111][112][113][114][115] Clearly, efforts to advance understanding of the roles that covalency and electronic structure play in governing chemical and physical properties would benefit from broader integration of synthetic, spectroscopic, and theoretical research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Single arene -f-block π-and δ-(back)bonding interactions have been used for C-H bond functionalisation 12 , and to stabilise the unusually low formal oxidation state of U II [13] , while bis(arene) sandwich molecules have been made for all areas of the periodic table except the actinides, where only predictions of stability exist 14 . A desire to better understand the subtlest actinide π-and δ-symmetry 60 bonding interactions has led us to the flexible macrocycle H 2 L Ar trans-calix [2]benzene [2]pyrrole 15 , which can geometrically and electronically mimic two cyclopentadienyl ions i.e.…”
mentioning
confidence: 99%
“…Figure 2c shows the molecular structure of complex 3, described below, which represents the first structural characterisation of a metallocene-type geometry for a Np III centre. Given the strong stabilisation afforded to Np III by (L Ar ) 2-, and recent landmark syntheses of formally Th II 135 and U II complexes 13,24 , we added the reductant NaK 3 to a 1,2-dimethoxyethane (dme) solution of 1, which turned purple black, and precipitated KCl, Figure 3a. The Vis-nIR spectrum of the supernatant ( Figure 3b) has broad absorptions with extinction coefficients centred around 600 nm and 1275 nm, characteristic were not pursued owing to the intrinsic unreliability of the approach for a system with five unpaired 5f electrons and (most likely) highly multiconfigurational excited states.…”
mentioning
confidence: 99%